2022
DOI: 10.1186/s12874-022-01625-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Potential Factors Associated with High HIV viral load in KwaZulu-Natal, South Africa using Multiple Correspondence Analysis and Random Forest Analysis

Abstract: Background Sustainable Human Immunodeficiency Virus (HIV) virological suppression is crucial to achieving the Joint United Nations Programme of HIV/AIDS (UNAIDS) 95–95-95 treatment targets to reduce the risk of onward HIV transmission. Exploratory data analysis is an integral part of statistical analysis which aids variable selection from complex survey data for further confirmatory analysis. Methods In this study, we divulge participants’ epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This is in line with findings of previous ML findings. 38 , 39 , 52 Furthermore, duration on ART was an important feature for predicting virological failure. Participants who had a longer duration of stay on ART had a higher risk of developing virological failure; this is consistent with the previous studies, 38 , 39 which reported longer ratio of follow-up increases the chances of developing virological failure.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings of previous ML findings. 38 , 39 , 52 Furthermore, duration on ART was an important feature for predicting virological failure. Participants who had a longer duration of stay on ART had a higher risk of developing virological failure; this is consistent with the previous studies, 38 , 39 which reported longer ratio of follow-up increases the chances of developing virological failure.…”
Section: Discussionmentioning
confidence: 99%
“…MCA has been widely used in various studies, including cancer and COVID-19 studies. [19][20][21][22][23] The standardized score or z-score was calculated at each time point using the formula z = (x−μ)/σ, where x represents the raw value, μ represents the mean, and σ is the standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that using machine learning algorithms, especially RF, is a promising methodology for analzying cross-sectional studies, showing robust predictive power and the ability to identify predictors of major importance. So far, this methodology has previously been used to evaluate factors with the greatest impact on high HIV viral load, COVID mortality, or presence of Bovine Viral Diarrhoea Virus [ 30 , 31 , 32 ], among others, but this is the first study of its application in CF and TA.…”
Section: Discussionmentioning
confidence: 99%